Way To Illustrate - Yogi Pratama (IC-ITECHS, 2020)
Even though design and art are important for the society, they are still considered different and separated one to another because of their different usability. Actually, both of them are inseparable. Design and art are created using the same fundamental art skills called illustration. Illustration is originated from narrative text which is interpreted into pictures. Illustration is known as the gray area of the world of art and design even though both of them use illustration for different purposes. It is also hard to categorize illustration as an art or as a design. This paper explains and discusses the general interpretation and knowledge of illustration. It can be found in the paper the definition of illustration and the reasons on the need of making illustration. It is also discussed in the paper how to make the illustration manually and digitally. The different types of illustration for different media, such as editorial book and other media, are also explained in detail. In conclusion, this study was conducted for giving a glimpse of what an illustration is and for suggesting answers to the debate whether the illustration is part of art or part of design.